Towards automation of the Swedish property formation process: A structural and logical analysis of property subdivisio - Hjelmblom, Magnus; Paasch, Jesper M.; Paulsson, Jenny; Edlund, Marina; Bökman, Fredrik (Nordic Journal of Surveying and Real Estate Research, 2019)
The ongoing digitalization of public administration and increased automation of legal decision-making bears promise to benefit citizens, businesses and other stakeholders through simpler and more efficient civil processes, and thus has great impact on the urban planning and building process. However, automation of decision-making that is directed or constrained by normative systems such as laws, regulations and policies, requires a detailed and accurate representation of these concepts and their constituent parts, and the domain to which they are applied. In this paper, we combine two perspectives on formalisation and classification of legal relations within the urban planning and building domain. In a cross-disciplinary fashion, we analyse and describe a small part of this domain at a higher level of abstraction and formalization using two different analysis instruments. Using these tools, we perform structural and conceptual as well as logical analyses of two specific snapshots of a fictitious property subdivision case in Sweden, focusing on the legal relations between different entities and parties involved in the specific situations. The structural analysis uses the Land Administration Domain Model ISO 19152:2012 standard formalism, and the logical analysis is based on the notion of atomic types of legal relations. We discuss some of the strengths and weaknesses of the two tools regarding the formal representation of rights, restrictions and responsibilities of different parties in the land administration domain, as well as how the tools relate to each other and how they can be aligned. We thus take one step towards a deeper understanding of the domain, and identify areas for future research that may provide better conditions for efficient and transparent use of geospatial information, and automation of the property subdivision process and other related civil processes.